Dynamic characteristics of a mobile robot manipulator built on the basis of a mechanism with parallel kinematic couplings - Strutynsky, V. B.; Yurchishin, O. Ya.; Kravets, O. M.; Polunichev, V. E. (НТУ "ХПІ", 2018)
The mathematical model of dynamical characteristics of a mobile robot with parallel kinematic bonds is developed on the basis of the use of the theory of fuzzy sets. For the dynamic system platform, four partial dynamic subsystems are introduced. Three of them describe the translational movement of the platform in three directions, and the subsystem of the spherical motion describes the rotary motion of the platform relative to the pole. Dynamic subsystems of a variable-length rod take into account the distribution of the parameters of the rod in length. The mathematical modeling of dynamic processes in mobile works of parallel kinematics at single and packet pulse dynamic shock disturbances is carried out.

Розроблена математична модель динамічних характеристик мобільного робота з паралельними кінематичними зв’язками на основі використання теорії нечітких множин. Для динамічної системи платформи введено чотири парціальні динамічні підсистеми. Три з них описують поступальні переміщення платформи у трьох напрямках, а підсистема сферичного руху описує поворотний рух платформи відносно полюса. Динамічні підсистеми штанг змінної довжини враховують розподіленість параметрів штанг по довжині. Проведено математичне моделювання динамічних процесів мобільного роботах паралельної кінематики при одиничних і пакетних імпульсних динамічних збуреннях штанг.
Keywords: mathematical modeling; multi-coordinate mobile robots; parallel kinematics; dynamic system; динамічні характеристики; мобільні роботи; математичне моделювання